ANALISIS JALUR PERILAKU KONSUMEN DALAM BERMEDIA SOSIAL DAN CITRA USAHA TERHADAP MINAT BERKUNJUNG KE RUMAH MAKAN MIE AYAM - Diana Ambarwati; Anita Sumelvia Dewi (Istithmar: Jurnal Studi Ekonomi Syariah, 2018)
This study aims to determine the total direct and indirect effects of consumer behavior in social media on the interest in visiting the Pak Kumis Chicken Noodle restaurant greater than 0.5 (50%). In this study, researchers conducted an associative approach with the variables studied, namely consumer behavior in social media taking, visiting interest and business image. The population in this study were 29 consumers who visited the Pak Kumis Chicken Noodles restaurant in Kediri and were willing to fill out the questionnaire in the middle of January 2018. The data analysis used path analysis techniques and sampling techniques using purposive sampling technique. Data collection techniques are carried out by conducting a survey to the research location through a questionnaire by submitting the questions to be filled in by the respondent in the middle of January 2018. From this study, it can be concluded that consumer behavior in social media directly influences the interest of visitation, consumer behavior in social media does not have an indirect effect through corporate image, and interests have an indirect effect through corporate image. The other variables that can affect the interest of visitation such as promotion, suitability between wants and needs, and other things that need to be considered for future research. It is hoped that there will be other variables that influence the interest of visitation which need to be considered by the next researcher or object of research.